Industrial Disputes Management and Academic Staff Welfare Improvement in Nigerian Universities - TAIWO, Ezekiel; AKINBODE, James; AKINRINLOLA, Morohunmubo Olayinka; OLU-OGUNLEYE, Itunu (Journal of Research in Educational Sciences; Vol 15 No 2 (2024): JRES Volume XV, Issue 2(18), Winter 2024DO - 10.14505/jres.v15.2(18).03, 2024)
There is a growing need to address the unique challenges of academic staff in universities such as unsatisfactory welfare and incessant disputes. In this regard, industrial dispute management was looked into as a tool to improve the welfare of academic staff in Nigeria. The study adopted the quantitative research approach and descriptive research design. The population of the study was academic staff from six federal universities in Southwest, Nigeria. A sample size of 377 was determined using the Taro Yamane sample size determination and was distributed to the selected Universities based on their respective population. The study sourced for primary data through which a structured questionnaire that was administered online to academic staff. Data collected were analysed with inferential statistical techniques such as correlation and regression analysis. The study found that collective bargaining has significant negative impact on the welfare of academic staff in the universities investigated (β=-0.494, p<005 ). Similalry, industrial communication had a negative significant impact on the welfare of academic staff in the universities investigated (β=-0.438, p<005 ). Furthermore, joint consultation had a negative significant impact on the welfare of academic staff in the universities investigated (β=-0.462, p<005 ). It was also revealed that industrial democracy had a negative significant impact on the welfare of academic staff in the universities investigated (β=-0.319, p<005 ). It was concluded that the existing industrial disputes management tools are not helping out in improving academic staff welfare in the universities. The study recommends a new approach to improving academic welfare without disputes.